Case Report: Primary aortoduodenal fistula caused by a 30-mm inflammatory abdominal aortic aneurysm - Akabane, Kentaro; Tajima, Yuta; Toyama, Shuji; Tamate, Yoshihisa; Watanabe, Tetsuo; Uchida, Tetsuro (Frontiers in Surgery, 2025)
Primary aortoduodenal fistula (PADF) is a rare but fatal condition with a high mortality rate. Among these, an even smaller subset is caused by an inflammatory abdominal aortic aneurysm (IAAA). Controlling hemorrhage and infection is the primary concern for lifesaving treatments. The standard treatment involves radical open surgery, although endovascular surgery is considered depending on the patient's condition and emergency. Currently, the optimal surgical strategy remains controversial. This study describes the surgical management of a rare case with PADF caused by an IAAA, highlighting challenges in treatment. A 71-year-old man was referred to our hospital following a sudden massive melena. Computed tomography revealed PADF caused by a suspected IAAA. Emergency anatomical reconstruction, fistula closure, and omental coverage via laparotomy were subsequently conducted. After the primary surgery, the patient experienced two episodes of hemorrhagic shock due to infection-induced rupture at proximal and right leg anastomosis sites, which were treated with endovascular repair. The patient was discharged 3 months after the initial surgery. However, 1 month after discharge, a pseudoaneurysm was discovered at the proximal anastomosis site caused by re-infection-induced rupture, and extra-anatomical reconstruction was performed. Excessive surgical invasion caused disseminated intravascular coagulation, and the patient died 1 week postoperatively. The prognosis for PADF management remains poor. Endovascular repair for emergent hemostasis is effective; however, the appropriate timing of radical surgery for prosthetic infection risk is unknown. Therefore, accumulating cases to establish the optimal treatment strategy and surgical timing is essential for improving survival rates.